Moderation of Islamic Messages Based on Cyber Media: Discourse Analysis on the nu.or.id and muhammadiyah.or.id Sites - Choirunissa, Shafira; Nurdin, Ali (Proceedings of International Conference on Da'wa and Communication, 2020)
The spread of radical ideology through cyber media was balanced by moderate journalism constructed by the journalism of Nahdlatul Ulama (NU) and Muhammadiyah. This study aims to understand the moderation construction of Islamic messages on the nu.or.id and Muhammadiyah.or.id sites. This research uses a constructivist approach with the kind of discourse analysis research model of Teun A. van Dijk. The results of the study describe that thematically, the two sites construct the Islamic message Wasathiyah. The schematic construction of the two sites is constructed with a news journalism frame. Semantic construction on the nu.or.id site emphasizes the connotative meaning of deviation, site; Muhammadiyah.or.id emphasized the importance of preventing religious deviations. Site syntax construction; nu.or.id emphasizes the connotative meaning, site; Muhammadiyah.or.id emphasized denotative meaning. Site stylistic construction; nu.or.id uses allegory figurative language, website; Muhammadiyah.or.id does not use a standardized language style. The rhetorical construction of the site; nu.or.id uses connotative sentences, site; muhammadiyah.or.id uses the phrase 'foreign' as a characteristic of the development of thought. The moderation construction of media cyber-based Islamic messages on both sites is presented in a tolerant manner, does not corner other religions, is fair, maintains a balance of news, and follows the latest events. The results of this study have contributed to the development of news writing based on peace journalism.